Pengembangan dan Pelatihan Konten Kreatif Dakwah Digital bagi Pimpinan Daerah Aisyiyah Kabupaten Jember - Syah Riza Octavy Sandy; Juhanda Juhanda; Muhlisin Rasuki (Jurnal Pengabdian Masyarakat, 2026)
The rapid development of information and communication technology has transformed the pattern of Islamic preaching from conventional methods to digital-based communication models. Islamic organizations are required to adapt to this transformation in order to expand the dissemination of religious messages in the digital era. However, the digital da’wah activities of the Aisyiyah Regional Leadership (PDA) of Jember Regency are still limited in terms of creative content production and digital communication strategies. This community service program aims to improve digital da’wah capacity through training and mentoring in the development of creative digital content such as videos, graphic designs, and copywriting. The implementation method consisted of three stages: socialization, module development, and training activities. The results of the program show that participants experienced increased understanding of digital da’wah strategies and improved technical skills in producing creative digital content. In addition, the program produced a digital da’wah guideline module that can be used as a reference for sustainable digital content management.